ASSESSMENT OF FUNCTIONAL MOBILITY IN PATIENTS AFTER UNILATERAL KNEE ARTHROPLASTY USING THE TIMED UP AND GO (TUG) TEST: A PRELIMINARY STUDY (CIPEEX, 2025)
Introduction: Knee osteoarthritis is a progressive musculoskeletal condition that causes pain and functional limitation. Initial treatment is usually conservative, and as the disease progresses, surgical treatment is indicated, with knee arthroplasty being the last option to restore quality of life and lower limb function. Objectives: To evaluate and compare functional mobility in patients undergoing unilateral knee arthroplasty with two types of prostheses, using the Timed Up and Go (TUG) test. Methods: Participants were evaluated at two time points after knee arthroplasty (18 fixed/18 rotational): the first after 17 months and the second after 42 months, on average. Functional mobility was assessed using the TUG test, where spatio-temporal parameters were collected using the G-Walk portable inertial sensor. After the initial assessment, the TUG was repeated after 2 years. Results: The average TUG time increased from 14.47s to 15.24s, with no significant difference between prosthesis types (p=0.456). In the Sit-to-Stand phase of the TUG, duration and acceleration decreased (1.83 s to 1.66 s and 4.08 m/s² to 3.69 m/s², respectively, p=0.03) for both groups. The rotation phase showed a significant increase in speed (54.62°/s to 68.74°/s; p
Keywords: Functionality; Timed Up and GO test; Knee arthroplasty